Effect of Bypass Fat and Fibrolytic Enzymes on Milk Yield and Milk Composition of Surti Buffaloes - Movaliya, Jignesh. K.; Kumar, Brishketu; Rao, Krishna S.; Patel, Vipul. R.; Raval, Ajay P. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The investigation was planned to study the effect of bypass fat @ 1 and 2 % of DMI with exogenous fibrolytic enzymes (EFE)  supplementation for 150 days on nutrients utilization and milk production in lactating buffaloes. Recently calved twenty-four lactating  buffaloes were assigned to four different treatment groups (n=6 animals in each) that included control, EFE (8 g mixture containing an  equal proportion of cellulase minimum 100000 IU/g and xylanase minimum 50000 IU/kg) alone, and EFE with bypass fat @ 1 % and 2 %  of DMI, respectively. The digestibility trial of seven days was conducted at the end of the experiment. Any treatment did not influence  feed, dry matter and nutrients intake in buffalo. EFE supplementation alone or with 1% bypass fat had significantly (p
Keywords: Buffaloes; Bypass fat; Digestibility; Exogenous fibrolytic enzymes; Milk production; Milk compositions